Therapist-reported alliance: is it really a predictor of outcome? - Zilcha-Mano, Sigal (J Couns Psychol, 2015)
Most of the literature on the alliance-outcome association is based exclusively on differences between patient reports on alliance. Much less is known about the unique contribution of the therapist’s report to this association across treatment, that is, the association between therapist-reported alliance and outcome over the course of treatment, after controlling for the patient’s contribution. The present study is the first to examine the unique contribution of the therapist-reported alliance to outcome, accounting for reverse causation (symptomatic levels predicting alliance), at several time points in the course of treatment. Of 156 patients randomized to dynamic supportive-expressive psychotherapy, antidepressant medication with clinical management, and placebo with clinical management, 149 were included in the present study. Alliance was assessed from the perspective of both the patient and the therapist. Outcome measures included the patients’ self-reported and diagnostician-rated depressive symptoms. Overall, the findings demonstrate that the therapists’ contribution to the alliance-outcome association was explained mainly by prior symptomatic levels. However, when a time lag of several sessions was introduced between alliance and symptoms, a positive association emerged between alliance at one time point and symptomatic distress assessed several sessions later in the treatment, controlling for previous symptomatic level. The findings were similar whether or not we controlled for the patient’s perspective on the alliance. Taken together, the findings attest to the importance of improving therapists’ ability to detect deterioration in the alliance.